Determinan Terbentuknya Epibole (Rolled Under Epithelial) Pada Penyembuhan Ulkus Kaki Diabetik - Irma Puspita Arisanty; Yani Sofiani; Rizki Nugraha Agung; Fitrian Rayasari; Dian Noviati Kurniasih (Universitas Pahlawan Tuanku Tambusai, 2025)
Introduction: Diabetic foot ulcers (wounds) are chronic ulcers that require special treatment, one of which is to ensure that the wound edge epithelialization process goes well. Epibole is a wound edge complication where the epithelium rolls downward, preventing wound closure. Methods: This study is a cross sectional observation with a conscusive sampling method in diabetikic foot ulcer patients. Results: Statistical analysis of this study showed the incidence of epibole in diabetic foot ulcers was 18.3% (N=93) and showed no significant relationship between the characteristics of respondents, ulcer characteristics with the incidence of epibole in diabetic foot ulcers. Multivariate analysis showed that the determinant factor of epibole formation in diabetic foot ulcer healing was wound age with an OR value of 5.566. Chronic wounds aged ≥ 21 days have the characteristic of keratinocytes (epithelialization) that slow down (do not migrate) so that epibole is formed and the wound is difficult to close. Recommendation: The occurrence of epibole should be identified as soon as posible, so that it can be treated immediately and accelerate wound re-epithelial or closure.